The Role of Internal Control in Fraud Prevention: A Systematic Review of Global Evidence (2021-2025) - Tussi Sulistyowati; Pardomuan Pardosi; Khairil Anwar; Maria Yovita R Pandin; Amiartuti Kusmaningtyas (Yayasan Adra Karima Hubbi, 2025)
Background. This study employs a qualitative descriptive approach through a systematic review of Scopus-indexed journal articles on fraud prevention published between 2021 and 2025. An initial search using targeted keywords yielded 4,283 articles, which were refined through specific filters, resulting in 24 articles for full-text analysis. Purpose. The findings confirm that well-designed internal controls enhance governance, reduce fraud risks, and improve organizational performance across diverse contexts such as China, France, Jordan, and Egypt. Method. The effectiveness of internal controls is shaped by institutional ownership, audit quality, digital transformation, and IT integration. Anti-fraud strategies are closely tied to transparency, monitoring, and risk management, while institutional factors like mandatory audits and ownership reforms strengthen control systems. Results. These insights suggest that managers should invest in robust, technology-supported internal controls tailored to their institutional context. Conclusion. Future research should examine the evolving impact of digitalization and governance changes on internal control effectiveness, particularly in emerging markets and high-risk sectors.